Approximation of multipulse behaviour with current source inverters - König, Simon; Herold, Gerhard (2014 Electric Power Quality and Supply Reliability PQ2014, 2014)
In comparison to those voltage source inverters (VSI) making only use of series inductors as filter elements current source inverters (CSI) must meet more specific demands regarding their applied switching schemes. The passive network at the terminals of these VSI then shows no resonant behaviour, whereas that of the CSI does. The reason for this are the output capacitors. Without them the CSI would not be able to feed escalating currents into the grid. That is the reason why even CSI multilevel-topologies cannot just so be operated using fundamental frequency switching schemes. Therefore mostly high-frequent switching schemes are research topics. They shall enable the inverter to avoid the resonance area in its generated output spectrum. For example the broadly used space vector pulse width modulation (SVPWM) is not able to immanently avoid low-order harmonics. It arbitrarily causes -5th and +7th order harmonics, even if only in a small degree. This paper therefore wants to point out the possibility to operate several standard CSI topologies in parallel to achieve multipulse behaviour. A 12-pulse behaviour can be reached exactly, whereas 18- or higher-pulse inverters can only be approximated with the demonstrated approach. Those topologies would be able to avoid resonance even when operated with fundamental frequency switching schemes. First the theoretical background will be given using the space phasor theory. Basic statements regarding the necessary topologies are also provided. © 2014 IEEE.
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.leen.approx
Keywords: Harmonics; Multi-pulse Current Source Inverter; Multilevel Current Source Inverter; Power Quality; Resonance